Nanoscale identification of local strain effect on TMD catalysis - Guo, Shasha (2025)
Strain engineering plays a crucial role in activating the basal plane of the TMD catalysts. However, experimental evidence linking strain strength to activity and distinguishing effects of compressive and tensile strain remains elusive due to the absence of high-resolution in situ correlation techniques. Here, we utilize nanobubble imaging by on-chip total-internal reflection microscopy to visualize active sites on the basal plane of strained MoS2 during hydrogen evolution reaction and atomic force microscopy to correlatively capture the nanoscale morphology and strain maps. By integrating the activity, morphology, and strain maps into comprehensive statistical analyses, we elucidate the strain effect on local activity at both multiprotrusion and (sub)single-protrusion levels. Our findings demonstrate that strain effectively activates sulfur vacancies on the basal plane, with tensile strain significantly enhancing local activity compared to compressive strain. Furthermore, we observe a time-dependent propagation of activity from high-activity to low-activity regions within single protrusions. This work clarifies the interplay between structural morphology and catalytic activity and provides new guidelines for the rational design of optimal TMD catalysts.